Pola Transformasi Aksi, Proses, Objek, dan Skema Mahasiswa dalam Memecahkan Masalah Limit Ditinjau dari Gaya Kognitif - Ayu Aristika (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to describe the transformation patterns of Action–Process–Object–Schema (APOS) in students with Field Dependent (FD), Field Neutral (FN), and Field Independent (FI) cognitive styles when solving limit problems. The central issue addressed in this research is the low level of conceptual understanding of limits among students. The study employs an exploratory qualitative approach with a collective case study design. The research subjects consist of nine mathematics education students selected based on the results of a cognitive-style assessment. Data were collected through APOS-based problem-solving tasks, observations of students’ thinking processes, and semi-structured in-depth interviews. The analysis reveals that FD students tend to remain at the action–process stages, FN students reach the process–object stages, while FI students construct conceptual understanding up to the object–schema stages. These findings indicate that cognitive style influences the depth and flexibility of students’ understanding of the limit concept. Theoretically, this study extends the application of APOS theory by incorporating cognitive style as a mediating factor. Practically, the results recommend implementing calculus learning strategies that are adaptive to students’ cognitive styles to strengthen conceptual transformation processes in advanced mathematics learning.